The clinical spectrum of reactions due to banana allergy - Dayıoğlu, Abdullah; Akgiray, Sena; Nacaroğlu, Hikmet Tekin; Bahçeci, Semiha (Bagcilar Training and Research Hospital, 2020)
Allergic reactions to bananas have rarely been reported. The clinic reports mostly moderate local allergic reactions (Oral Allergy syndrome) to bananas, though some reports state reactions reaching anaphylaxis. We report three cases of banana allergy. The first case, immediately after giving a teaspoon of banana to a 7-month-old baby by the mother, he was admitted to the emergency department with the complaints of vomiting, urticaria, swelling of the mouth and eyes. The second case, after some banana yogurt was eaten by a 6.5-month-old baby, she presented with a rash which developed at the 3rd hour. In the third case, a 16-year-old male patient applied with itchy rashes on his body after eating a banana in 1-2 hours. Our cases are presented to emphasize that urticaria and anaphylaxis may occur due to banana allergy.

Muza karşı alerjik reaksiyon nadir olarak raporlanmıştır. Muz alerjisinde klinik genellikle orta derecede lokal semptomlar (Oral Alerji sendromu) şeklinde bildirilmekte, ancak bazı raporlarda anafilaksiye kadar gidebilen şiddetli semptomlar da bildirilmiştir. Bu bildiride muz alerjisi tanısı alan üç olgu sunulmuştur. İlk olgu 7 aylıkken annesinin 1 çay kaşığı muz yedirmesinden hemen sonra fışkırarak kusma, ürtiker, ağız ve gözlerde şişlik şikayetiyle acile başvurdu. İkinci olgu 6,5 aylıkken yediği muzlu yoğurt sonrası 3. saatte gelişen döküntü şikayetiyle bize başvurdu. Üçüncü olgu olan 16 yaşındaki erkek hasta, muz yedikten 1-2 saat sonra vücutta kaşıntılı döküntüler ile başvurdu. Muz alerjisine bağlı ürtiker ve anafilaksi görülebileceğini vurgulamak için olgularımız sunulmuştur.
Muz alerjisine bağlı olarak gelişen reaksiyonların klinik spektrumu
Keywords: Anaphylaxis; Atopic Dermatitis; Banana Allergy; Anafilaksi; Atopik Dermatit; Muz Alerjisi